What will make my child's school safer? Parent perceptions of active shooter preparedness. Issue 3 (24th July 2020) - Wallace, Lacey Nicole
Abstract : Purpose: This study aims to examine parent perceptions of school active shooter preparedness and prevention efforts, as well as parent perceptions of the risk of an active shooter event. Design/methodology/approach: Data were obtained in 2019 through an online survey of 182 Pennsylvania residents who were the parents or step-parents of children enrolled in pre-Kindergarten, Kindergarten-12th or college/ university. Respondents were a subset of a state-representative sample of 668 individuals. Findings: Actions taken by schools were largely unrelated to parent perceptions. Parents who reported that their child's school had provided information about active shooters to students had better attitudes toward preventive efforts overall. Parents who reported that their child's school had changed firearms policy perceived a higher level of risk. Parents were also asked to share what they felt their child's school could do that would help them feel more prepared for an active shooter event. The most common response was for schools to install metal detectors or perform random metal detector checks. Originality/value: While there is extensive research on the views of students about school safety and security and, to a lesser degree, the views of school administrators and teachers, parents have largely been neglected in school safety research.